Philosophy of Islamic Constitutional Law: Shiite School Perspective - Bisri, Hasan (Research and Development Institution, Darussalam Institute for Islamic Studies, 2023)
The objective of this work is to expound upon Shiite philosophy and constitutional theory by drawing upon the views and ideology of Imam Khomeini. In addition, this research endeavours to compare the constitutional ideas of Shiite and Sunni factions. This study employs the methodology of literature review. Several primary and secondary sources pertaining to the research objectives were thoroughly reviewed, analysed, and compared. The study's findings indicate that within Shiite ideology, the power and control over authority are exclusively attributed to God. Allah is the ultimate arbiter of all natural phenomena and every entity within it. God possesses supreme authority, possesses dominion, and bestows legislation. According to this philosophical understanding of existence, it is necessary for human civilization to be guided by a leadership that is of divine nature. In Shi'a thought, Muhammad's role as a prophet and messenger of Allah entails not only the responsibility of communicating divine law (al-qanūn al-ilāhi), but also the duty of putting that law into practice.